Pengaruh Penggunaan Media Komik Terhadap Hasil Belajar Peserta Didik Kelas III Tema I Subtema I Di Mi The Noor - Nur Haqiqi; Benny Angga Permadi (Jurnal Riset Madrasah Ibtidaiyah, 2022)
The teaching and learning process carried out by teachers at MI The Noor school, especially in the use of learning media is still very lacking, this is evidenced by the learning outcomes of students who are still much below the KKM, besides that when the teaching and learning process is carried out, students are less enthusiastic in participating in lessons, This is very influential on the understanding of students, resulting in less achievement of the desired learning. Therefore, in the learning process, one must be able to choose the right media, comic media is very suitable for use in learning, because comics media can arouse the enthusiasm of students in the learning process, and also the material delivered with comic media is very clear and simple so that it will affect the learning process. student learning outcomes. This study aims to determine the effect of using comics media on the learning outcomes of third-grade students, Theme I, Sub-theme I. The research design is One Group Pretest Posttest. The study population consisted of 88 students in classes I, II, III, IV, V, VI and 16 students in class III as samples. The results of data analysis using the Paired sample t-test test obtained the value of Sig. (2-tailed) of 0.000, which means that the test results obtained a value smaller than 0.05, so it can be concluded that there is an influence in the use of comic media on student learning outcomes.